XRD Study of Indium Oxide Film Deposited by Sol-Gel Spin Coating. - Caglar, Mujdat; Ilican, Saliha; Caglar, Yasemin; Yakuphanoğlu, Fahrettin (Int Union Crystallography, 2009)
[Abstract Not Available]
Keywords: metal oxides; sol-gel method; X-ray diffraction and structure